DYNAMICS TOPOGRAPHY MONITORING IN PEATLAND USING THE LATEST DIGITAL TERRAIN MODEL - Julzarika, Atriyon; Aditya, Trias; Subaryono, Subaryono; Harintaka, Harintaka (Journal of Applied Engineering Science, 2022)
The Central Kalimantan province in Indonesia has one of the country’s largest peatlands. The Peatland has dynamic topographic conditions that cause land subsidence or uplift in water levels. Monitoring the topographic dynamics conditions of this Peatland requires an up-to-date DTM capable of presenting the latest conditions. Monitoring with the latest DTM is needed because there is currently no method suited to large-scale, cost-effective mapping. This study aims to monitor the dynamics of topography in Peatland using the latest DTM. The latest DTM is a combination of the DTM master and the latest displacement. The novelty of this research is in monitoring the dynamics of Peatland with the latest DTM every rainy and dry season. DTM master is DTM extracted from InSAR ALOS PALSAR-2. Displacement was obtained from DInSAR extraction from Sentinel-1. The research area is located in Pulang Pisau, Indonesia. DTM master was extracted using InSAR in December 2017. Displacement was extracted every 6–7 months. The monitoring periods for dynamics topographic were January 2018, August 2018, January 2019, July 2019, January 2019, and June 2020. Each period involved extracting the latest DTM and the displacement. The dynamics topography of the study area lies at the value of 1.5 m. This latest DTM can be used for 1: 20,000 to 1: 25,000 mapping. The latest DTM has a RMSE(z) of 0.705 m on the field measurement. This vertical accuracy-test uses 15 points from GNSS-levelling. Based on the RMSE (z) obtained, the vertical accuracy is 1.3818 m at the 95% confidence level.